2006
DOI: 10.1007/s00216-006-0497-z
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial behavior of sulforhodamine 101 at the polarized water/1,2-dichloroethane interface studied by spectroelectrochemical techniques

Abstract: The transfer mechanism of an amphoteric rhodamine, sulforhodamine 101 (SR101), across the polarized water/1,2-dichloroethane (DCE) interface was investigated using cyclic voltammetry, differential voltfluorometry and potential-modulated fluorescence (PMF) spectroscopy. The voltammetric response for the ion transfer of SR101 monoanion from water to DCE was observed as the diffusion-controlled transfer process. An unusual voltammetric response was found at 0.15 V more negative than the formal transfer potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Systematic electrochemical treatment did not begin until the late 1970's when Koryta et al 103 demonstrated that the liquid/liquid interface lends itself to the same formalism as a solution/ metal interface and that similar, if not identical, experimental methodology could be used. This led soon to development of various electrochemical techniques to study the liquid/liquid interface, including, among others, studies of the solvent dropping interface [103][104][105][106][107][108] , and studies of cyclic voltammetry 108 , impedance measurements [109][110][111][112] , drop pressure method 113 , galvanostatic pulse method 114,115 , stripping voltammetry 114 , voltfluorometry [116][117][118][119] , and transport across a microinterface [120][121][122][123][124][125] . Electron transfer and photoinduced electron transfer have been also observed on ITIES or theoretically treated 19,84,86,87,[126][127][128][129][130][131][132][133] , as well as electrochemical catalysis 19,126,127,134,135 , adsorption …”
Section: When Nernstmentioning
confidence: 99%
“…Systematic electrochemical treatment did not begin until the late 1970's when Koryta et al 103 demonstrated that the liquid/liquid interface lends itself to the same formalism as a solution/ metal interface and that similar, if not identical, experimental methodology could be used. This led soon to development of various electrochemical techniques to study the liquid/liquid interface, including, among others, studies of the solvent dropping interface [103][104][105][106][107][108] , and studies of cyclic voltammetry 108 , impedance measurements [109][110][111][112] , drop pressure method 113 , galvanostatic pulse method 114,115 , stripping voltammetry 114 , voltfluorometry [116][117][118][119] , and transport across a microinterface [120][121][122][123][124][125] . Electron transfer and photoinduced electron transfer have been also observed on ITIES or theoretically treated 19,84,86,87,[126][127][128][129][130][131][132][133] , as well as electrochemical catalysis 19,126,127,134,135 , adsorption …”
Section: When Nernstmentioning
confidence: 99%
“…The transfer of ionic species across the interface often involves the adsorption process [10][11][12] and following ion-association of adsorbed monomer species [13,14]. The elucidation of the potential dependent adsorption behavior would be a key point to understand the ion-transfer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…As in conventional solid electrode|solution electrochemistry, the current can arise from electron transfer across ITIES and additionally it can also arise from the transfer of ions across ITIES [13][14][15][16][17]. This renders the ITIES ideally suited to the study of ion partitioning across two immiscible phases, which combined with traditional techniques allows for the contribution of ions and neutral compounds to be determined, as shown in the studies of Bouchard et al [18,19], Reymond et al [11], and Nagatani et al [20]. Partition coefficients are simply a measure of solute's affinity for either phase of a liquid|liquid system, as are Gibbs energies of transfer across the ITIES, and therefore the two are directly related.…”
Section: Determination Of Partition Coefficientsmentioning
confidence: 99%
“…In the paper of Kontturi and Murtomäki [10], 1,2-dichloroethane (DCE) was chosen as a replacement for noctanol, because of their similar electrical properties, including relative permittivity and dipole moment, and the fact that DCE is sufficiently polarisable to allow the transfer of ions across the water|DCE interface. The water|DCE system has now become the standard for determining partition coefficients of drugs using the ITIES [20][21][22][23]. Kontturi and Murtomäki [10] determined partition coefficients at aqueous pH ≈ 2, at which the drugs under investigation existed in a protonated form.…”
Section: Determination Of Partition Coefficientsmentioning
confidence: 99%